(untitled) (International Journal of Built Environment and Sustainability, 2025)
The dramatic rise in the aging population has become a formidable global phenomenon, especially in developing countries, including Malaysia. A retirement village or modern senior living facility is a new residential typology for older people to cater to an increasing number of aging population in Malaysia. This study investigates the spatial characteristics of sustainable design of aging facilities. A case study of the Kampung Admiralty in Singapore is chosen due to its prominence. The spatial design qualities of the selected case study are meticulously examined using the space syntax analysis to evaluate the level of permeability and wayfinding. A qualitative research method is applied via the space syntax’s justified graph and visibility graph analysis (VGA) using the DepthmapX simulation program. The outcome of the study finds that Kampung Admiralty is a well-designed retirement village typology embodying a spatial configuration that promotes social interaction among visitors and senior residents. Ultimately, the study underscores the overall space syntax performance of Kampung Admiralty, which is dominated by semi-public spaces accounting for 47.62% which corresponds to the ’easy’ permeability and high level of clarity in the wayfinding. In essence, the study found that the Kampung Admiralty has excellent level of permeability and wayfinding in the spatial configuration to meet the basic needs of the elderly residents. Therefore, the spatial planning of Kampung Admiralty can become an outstanding reference when designing a retirement village in an urban area.